Epidemiology and Clinical Features of Listeriosis in Gipuzkoa, Spain, 2010–2020 - Vallejo, Pedro; Cilla, Gustavo; López-Olaizola, Maddi; Vicente, Diego; Marimón, José María (Frontiers in Microbiology, 2022)
Background Listeriosis continues to be one of the most important notifiable foodborne diseases. Nonetheless, in Spain, there are few data on the molecular epidemiology of Listeria monocytogenes infections in recent years. Aim To describe clinical features and the molecular epidemiology of human listeriosis over an 11-year period (2010–2020) in Gipuzkoa, Northern Spain. Methods A total of 111 isolates, all but one from invasive disease, were studied. Serotyping (agglutination and multiplex polymerase chain reaction [PCR]) and multilocus sequence typing were performed for all isolates. Antibiotic susceptibility was assessed by the broth microdilution method. Results The average annual incidence of listeriosis in non-pregnancy-associated cases was 1.55 per 100,000 population, with a 1-month mortality rate of 22.2%. In pregnant women, the average incidence was 0.45 cases per 1,000 pregnancies. Twenty-four sequence types were identified, serotype 4b ST1 (24.3%) being the most frequent followed by 1/2b ST87 (18.9%), which caused two long outbreaks in 2013–2014. A significant association was observed between ST219 and meningitis (p < 0.001). All isolates were susceptible to ampicillin as well as other antibiotics used in listeriosis treatment. Conclusion Despite current control measures, listeriosis continues to be an important cause of mortality in the elderly, preterm birth, and miscarriages in pregnant women. Improvements in the control and diagnosis of listeriosis are needed to reduce the impact of this infection on vulnerable populations.